Flesh, Wires and Forest. Trans* Potentialities, Agency and Erotic Pleasure in some Galician Dystopias - Calderón Puerta, Aránzazu (Madrygal. Revista de Estudios Gallegos, 2023)
The aim of this paper is to analyse and interpret four Galician erotic science fiction stories, focusing on three aspects: the trans* body as an articulation of the posthuman condition, the role of sex and erotic pleasure as biopolitical technologies in dystopias, and the concept of agency implicit in them. Different corporealities recreated in these stories escape familiar taxonomies, problematising traditional concepts of subjectivity and agency as exclusively human factors (Barad 2012). These literary texts question the current gender system from different places and perspectives, denaturalising it. The varied trans* bodies of the protagonists represent different potentialities, unpredictable scripts of being in the world, possibilities of a future that does not reproduce the current hegemonic model of bodies, gender, species, race, class or disability. They move us away from heterocolonial reproductive futurity (Preciado 2020) and bring us closer to new models of kinship by evidencing interspecies dependency (Braidotti 2015) through new proposals –not as futuristic as it might seem at first– of “other”, monstrously fascinating corporealities.
Keywords: Trans* Bodies; Posthumanism; Gender; Galician Science Fiction; Erotica